“O palco onde estreia a história chapadense” – acervo Fotográfico e documental da colonização e formação do distrito de Tesouras (1915 – 2000) - Mattje, Michele Kunrath (2023)
Chapada, a city with less than 10 thousand inhabitants, located in the northern region of Rio Grande do Sul, has its origins in the Tesouras District. The territory belonged to José Sampaio and Antônio Sampaio, farmer brothers from this region. Being a colonization nucleus particular, had Miguel Matt as an intermediary colonizer. With the announcements of good lands, fertile and with a good market price in this region, many colonizers went in search of acquire these lands and migrate to them, coming mainly from the cities of São Sebastião do Caí, Montenegro, São Leopoldo and Lajeado. The colonization of Tesouras began in 1916, which, in 1921, became belong to the Municipality of Palmeira das Missões, as the 10th District, by Municipal Act nº 41 of December 1, 1921. The administrative division of the municipality of Palmeira in 1933, if refers to these lands as “Colônia Tesouras”, changing its name to Tesouras from the administrative divisions from 1937 (IBGE, 2023). In 1921 there were already around 300 inhabitants in the locality, which was named Tesouras due to the existence of a bush that had the shape of a bird, in addition to the large presence of the Earwig bird in this region (STEFFEN, STEFFEN, STEFFEN, 1984, p. 12).